Photoelastic Analysis of Cemented or Screwed Implant-Supported Prostheses With Different Prostheses Connections - Tonella, Bianca Piccolotto [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Ferraco, Renato [UNESP]; Falcon-Antenucci, Rosse Mary [UNESP]; Perri de Carvalho, Paulo S.; Goiato, Marcelo Coelho [UNESP] (Allen Press Inc, 2011)
The aim of this study was to evaluate the stress distribution of different retention systems (screwed or cemented) associated with different prosthetic connections (external hexagon, internal hexagon, and Morse taper) in 3-unit implant-supported fixed partial dentures through photoelasticity. Six models were fabricated with photoelastic resin PL-2, and each model contained two implants of 4.0 x 10.0 mm. The models presented different retention systems (screwed and cemented) and different connections (external hexagon, internal hexagon, and Morse taper). The prostheses were standardized and fabricated in Ni-Cr alloy. A circular polariscope was used and axial and oblique (45) loads of 100 N were applied in a universal testing machine. The results were photographed and analyzed qualitatively with a graphic software (Adobe Photoshop). The screwed retention system exhibited higher number of fringes for both axial and oblique loadings. The internal hexagon implant presented better and lower stress distribution for both cemented and screwed prostheses. The oblique loading increased the number of fringes in all models tested. The cemented retention system presented better stress distribution. The internal hexagon implant was more favorable according to the biomechanical standpoint. The oblique load increased stress in all systems and connections tested.
Keywords: dental implants; fixed partial denture; implant-supported fixed partial denture